Unusual presentation of metastatic malignant melanoma: a case report. Issue 2 (25th October 2020) - Sah, Mukesh Kumar; Barakoti, Rimmy; Shrestha, Nirajan; Gautam, Neha; Sharma, Upama; Kafle, Monique
Abstract : Introduction: The presentation of metastatic lesion of malignant melanoma (MM) may be unusual, as this case, in which the lesions were multicystic swelling over right arm and necrotized swelling at right chest wall. Identifying the unusual variants of MM is important to allow application of the most appropriate treatment strategies before something wrong happens. Methods: This case report has been prepared following the SCARE guideline 2018, a surgical case report guidelines. Presentation of the case: A 60-year-old man presented with a 14-month history of swelling on right arm and anterior chest wall with the chief complain of blackish discharge from the latter. Six months ago, he amputated his right thumb for melanoma after a histopathology evaluation. It was an unusual presentation of a metastatic lesion of MM. On the basis of the histopathology report, the final diagnosis of our patient was subcuticular metastatic MM which has a very poor prognosis. According to TNM classification, the final diagnosis of the case was T4b N0 M1a . Although he has been under regular follow-up, the lesions are still present and his health condition is deteriorating. Discussion: Metastatic melanomas are often rare; their misdiagnosis potentially jeopardizes patients' health and survival, and have medico-legal implications. Melanoma often has a protracted disease course, in which patients have a disease-free period following surgical excision of the primary tumor, only to discover visceral metastases—months, years, or even decades later. Melanoma metastasis is an ominous sign as it generally predicts a poor prognosis. This case is an unusual presentation of metastatic melanoma where, with the elaboration of history and proper examination of lesion, the diagnosis of metastatic melanoma was made. Conclusion: Metastatic MM has a very poor prognosis and an early diagnosis with clinical presentation is very essential in a country where health facilities are not well developed. Knowing the unusual variants of MM is important to allow application of the most appropriate treatment strategies before something wrong happens.